Red Cell Distribution Width to Albumin Ratio versus Red Cell Distribution Width to Platelet Ratio as Predictors of 28-Day Mortality in Sepsis Patients Admitted to the Intensive Care Unit - Ningsih, Diana Fitria; Pison, Osmond Muftilov; Suwarman, Suwarman; Maskoen, Tinni T.; Oktaliansah, Ezra; Aditya, Ricky (Faculty of Medicine, Universitas Padjadjaran, 2025)
Background: Sepsis is a leading cause of mortality in the Intensive Care Unit (ICU). Early identification of high-risk patients requires simple and accessible prognostic biomarkers. The Red Cell Distribution Width to Albumin Ratio (RAR) and Red Cell Distribution Width to Platelet Ratio (RPR) have been proposed as potential biomarkers.Methods: This prospective cohort study was conducted in the ICU of Dr. Hasan Sadikin General Hospital, Bandung, from July to September 2025, involving 71 subjects who met the Sepsis-3 criteria. RAR and RPR values were calculated from blood tests within the first 24 hours of ICU admission. The primary outcome was 28-day mortality. Statistical analysis used the Receiver Operating Characteristic (ROC) curve to determine the cut-off value, sensitivity, specificity, and Area Under the Curve (AUC). The AUC comparison between RAR and RPR was analyzed using the DeLong test.Results: A total of 41 patients (57.7%) experienced 28-day mortality. The optimal cut-off value for RAR was 5.7404 (Sensitivity 85.4%; Specificity 73.3%) with an AUC of 89.3% (95% CI: 79.8–95.4%). The optimal cut-off value for RPR was 0.0627 (Sensitivity 75.6%; Specificity 76.7%) with an AUC of 74.7% (95% CI: 63.0–84.3%). RAR had a significantly better discriminatory value than RPR (p=0.026).Discussion: The RAR value is a better predictor of 28-day mortality than the RPR value in septic patients treated in the ICU.Conclusion: RAR can be considered a simple and effective prognostic tool for the early risk stratification of septic patients.